Hubungan Penggunaan Sosial Media Dengan Hasil Belajar Pada Remaja Kelas Xi Di Smkn 1 Padang Tahun 2024 - Ramadini, indri; Figo Rahmadia; Murniati Muchtar; Heppi Sasmita; Wira Heppy Nidia (Jurnal Amanah Kesehatan, 2025)
In 2018, around 54.68% of Indonesia's population used social media with the majority of users being 72.41% teenagers. Excessive use of social media can reduce students' learning motivation. This decrease in students' learning motivation has an impact on their learning outcomes. This is because most students who have joined social media spend more time opening this networking site than studying. This research aims to determine the relationship between the use of social media and the learning outcomes of class XI students at SMKN 1 Padang. This type of research is quantitative correlational research with a cross-sectional design conducted at SMKN 1 Padang from October 2023- June 2024. The research population is all Class XI students at SMK N 1 Padang, totaling 427 students, with the number of male students as many as 413 people and the number of female students was 14 people. The sample in this study amounted to 108 respondents. The type and technique of data collection is primary data using a questionnaire. The statistical test used is Chi Square. The research results showed that almost all respondents, namely 96 people (88.9%) had high learning outcomes and almost all respondents, namely 101 people (93.5%) used social media at a moderate level. The bivariate test results show a p value = 0.626. There is no significant relationship between the use of social media and the learning outcomes of class XI students at SMKN 1 Padang.